2021
DOI: 10.7759/cureus.17733
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Neutrophil/Albumin Ratio and Early Mortality After Major Lower Extremity Amputation

Abstract: IntroductionDiabetic foot infection is a condition that affects the patient's life, may cause limb loss, and has a high mortality. Too many parameters were used for predicting early mortality but the gold standard method wasn't described. Neutrophil lymphocyte ratio (NLR) is universally accepted as a predictive value for amputation-free survival and mortality. NLR increases due to inflammation-induced neutrophilia and lymphopenia related to cortisol-induced stress. Increasing in the neutrophil albumin ratio is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Lastly, unfavorable clinical outcomes occurred more frequently in group HH than in groups HL and LL; however, there was no significant difference in the incidence of unfavorable clinical outcomes between Groups HH and LH. Similar to our results, a previous study investigating the relationship between NAR and early mortality after major lower extremity amputation found that the preoperative NAR had lower sensitivity and specificity than postoperative NAR for mortality prediction 22 . Although both pre- and postoperative NARs were associated with unfavorable clinical outcomes in our study, postoperative NAR was a better predictor of unfavorable outcome than preoperative NAR.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Lastly, unfavorable clinical outcomes occurred more frequently in group HH than in groups HL and LL; however, there was no significant difference in the incidence of unfavorable clinical outcomes between Groups HH and LH. Similar to our results, a previous study investigating the relationship between NAR and early mortality after major lower extremity amputation found that the preoperative NAR had lower sensitivity and specificity than postoperative NAR for mortality prediction 22 . Although both pre- and postoperative NARs were associated with unfavorable clinical outcomes in our study, postoperative NAR was a better predictor of unfavorable outcome than preoperative NAR.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to our results, a previous study investigating the relationship between NAR and early mortality after major lower extremity amputation found that the preoperative NAR had lower sensitivity and specificity than postoperative NAR for mortality prediction. 22 Although both pre-and postoperative NARs were associated with unfavorable clinical outcomes in our study, postoperative NAR was a better predictor of unfavorable outcome than preoperative NAR.…”
Section: Discussionmentioning
confidence: 44%
“…NAR, consisting of neutrophil and Alb, is a promising biomarker for predicting the prognosis of cancer (44-47). Günay et al showed that higher NAR after lower extremity amputation was significantly associated with early mortality after extremity amputation (48). Chen et al found that NAR was related to allcause mortality in patients with stroke (49).…”
Section: Narmentioning
confidence: 99%